Answer:
B) y = x2 - 3
Explanation:
Suppose you have a function y = f(x), you can do these following operations on the function:
Shift up a units:
![y = f(x) + a](https://img.qammunity.org/2020/formulas/mathematics/college/gs62pl93a87mq0di1z902dop6eh3t3v7va.png)
Shift down a units:
![y = f(x) - a](https://img.qammunity.org/2020/formulas/mathematics/college/2qzfz6g02ja5gfwuakkroy1v5rlhspkrqk.png)
Shift left a units:
![y = f(x + a)](https://img.qammunity.org/2020/formulas/mathematics/college/skwa9xgxv99769zyy699ii181jb8v09gos.png)
Shift right a units:
![y = f(x - a)](https://img.qammunity.org/2020/formulas/mathematics/college/eba5m5zkht7qx37psv9hn5vcu4ucb9h2bl.png)
So the correct answer for this question is:
B) y = x2 - 3